Commercialising comparison: Pearson puts the TLC in soft capitalism. Issue 3 (3rd May 2016) - Hogan, Anna; Sellar, Sam; Lingard, Bob
Abstract: This paper provides a critical policy analysis of The Learning Curve (TLC) (2012), an initiative developed by the multinational edu-business, Pearson, in conjunction with the Economist Intelligence Unit. TLC exemplifies the commercialising of comparison and the efforts of edu-businesses to strategically position themselves in education policy processes globally. In analysing TLC, our account seeks to proffer a critical analysis of this emerging policy genre, and the way it functions as part of the new 'soft capitalism'. We analyse TLC in relation to Pearson's new business strategy, which emphasises corporate social responsibility and accountability to consumers for the efficacy of its products and services. We argue that Pearson is now generating and appropriating various data to legitimise its products and services according to a 'neo-social' mode of accountability. Network ethnography is employed to document the global networks of both people and data associated with TLC and we reflect on the emergence of Pearson as a potential education policy actor.